2023
DOI: 10.5829/ije.2023.36.10a.08
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Fiber-reinforced Concrete under Cyclic Loading using Extended Finite Element Method and Concrete Damaged Plasticity

S. El Yassari,
A. EL Ghoulbzouri

Abstract: In recent years, the scientific community has shown a growing interest in fiber-reinforced concrete (FRC) for modern structures due to its enhanced ductility compared to traditional reinforced concrete (RC). This paper introduces an analytical model that incorporates a comprehensive fiber reinforcing index (RI) to study various types of FRC. The analysis focuses on the compressive and tensile behaviors, damage evolution under cyclic loading, and crack propagation in the concrete matrix. To effectively simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The structural damage assessment of FRC has not been explored yet. It is very essential to determine the damage index (31)(32)(33)(34)(35)(36)(37)(38) of FRC for different percentage of fibre under different types of static and dynamic load. The investigation results from damage assessment may explore new important direction of research.…”
Section: Damage Assessmentmentioning
confidence: 99%
“…The structural damage assessment of FRC has not been explored yet. It is very essential to determine the damage index (31)(32)(33)(34)(35)(36)(37)(38) of FRC for different percentage of fibre under different types of static and dynamic load. The investigation results from damage assessment may explore new important direction of research.…”
Section: Damage Assessmentmentioning
confidence: 99%
“…FRP composites provide many benefits, such as high strength-to-weight ratio, resistance to corrosion, and ease of installation (3)(4)(5)(6). Yassari and Ghoulbzouri (7) numerically studied the behaviour of fiber-reinforced concrete subjected to cyclic loads using concrete damaged plasticity. They found that the concrete damaged plasticity improves the prediction of dynamic performance of fiber-reinforced concrete structures.…”
Section: Introductionmentioning
confidence: 99%
“…In several instances, material characteristics have been employed to simulate their behavior under real working conditions or relevant scenarios in analytical models. The behavior of structures exhibits responses under assigned loading conditions, which aids in investigating structural deformations such as damage, elasticity, plasticity, and vibration (31)(32)(33). Analyzing these responses indicates the structural component usage experienced during operational conditions, allowing for the prediction of fatigue and service life (34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%